Internalisasi Nilai-nilai Kebangsaan dalam Proses Pembelajaran - Sugeng Bayu Wahyono (MAJALAH ILMIAH PEMBELAJARAN, 2009)
One of the rumours that ought to receive attention of the Indonesian nation now is education have a national perception that is felt very much important if paying close attention to the development of the situation that is influenced with the disintegration threat of the nation. Education that has a national perception could diimplementasikan through the curriculum and heterogenous the other educational activity. With education that has a national perception, apparently the value and spirit of pluralism continue to experience the process of internalisation in each generation in areas so as to show the tolerant attitude, to appreciate each other and to act in a humanitarian way in the Indonesian Unitary State frame